FACTORS ASSOCIATED WITH BREASTFEEDING IN THE FIRST HOUR OF LIFE IN RIO BRANCO, ACRE, BRAZIL - Alanderson Alves Ramalho; Fernanda Andrade Martins; Thaíla Alves dos Santos Lima; Andréia Moreira Andrade; Rosalina Jorge Koifman (Universidade do Estado do Rio de Janeiro, 2019)
Objective: To determine the prevalence and to analyze factors associated with breastfeeding in the first hour of life in Rio Branco, Acre. Methods: A cross-sectional population-based study was conducted with 1144 mother / newborn binomials belonging to a maternal-infant cohort in Rio Branco, capital of Acre State, Brazil. The data were collected in the only two maternity hospitals in the capital. The dependent variable is breastfeeding in the first hour of life and its associated factors were identified through multiple and hierarchical logistic regression. Results: The prevalence of breastfeeding in the first hour of life in Rio Branco was 58.2% (95% CI: 55.2% - 61.2%). At distal and intermediate levels were associated with the outcome: maternal schooling, socioeconomic class, number of residents at home, maternal work and hypertension during pregnancy. In the proximal model, breastfeeding in the first hour of life was inversely associated with gestational hypertension (OR: 0.68, 95% CI: 0.47-0.98), cesarean section (OR: 0.15, 95% CI: 0.11-0.20) and low birth weight (OR: 0.32, 95% CI: 0.19 - 0.55). Conclusion: The main obstacles to breastfeeding in the first hour of life in Rio Branco are cesarean delivery and low birth weight. DOI: 10.12957/demetra.2019.43809